2004
DOI: 10.1021/cm0350683
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Arylene-Bridged Polysilsesquioxane Xerogels and Aerogels

Abstract: Arylene-bridged polysilsesquioxanes are an interesting class of porous materials prepared by sol−gel processing of ethoxysilane monomers in which there are two or more trialkoxysilyl groups positioned about an arylene bridging group. The majority of these materials are highly porous with surface areas as high as 1880 m2/g. In an effort to understand the nature of porosity in these materials, small-angle X-ray and neutron scattering were employed to characterize phenylene-, biphenylene-, and terphenylene-bridge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 58 publications
1
44
0
1
Order By: Relevance
“…In this work, the luminescent bridged polysislsesquioxanes were obtained by hydrolysis and condensation of the urea-based tris(silylated) monomer containing large organic bridging groups under acidic conditions. [26] The FTIR spectra of the monomer and the monomer with Eu 3+ (Eu 3+ /monomer ratio = 0.5) are shown in Figure 1. For the monomer, the ν(Si-C) and ν(Si-OEt) absorption bands characteristic of trialkoxysilyl functions appear at 1194 and 1080 cm -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, the luminescent bridged polysislsesquioxanes were obtained by hydrolysis and condensation of the urea-based tris(silylated) monomer containing large organic bridging groups under acidic conditions. [26] The FTIR spectra of the monomer and the monomer with Eu 3+ (Eu 3+ /monomer ratio = 0.5) are shown in Figure 1. For the monomer, the ν(Si-C) and ν(Si-OEt) absorption bands characteristic of trialkoxysilyl functions appear at 1194 and 1080 cm -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…54), 55) Since the surface of the gels derived from these precursors is highly hydrophilic, the organic bridging groups are deduced to be embedded inside the rigid siloxane networks resulted from hexafunctionality, and do not contribute to the mechanical properties and hydrophobicity. Flexible networks with low crosslinking density, low residual silanol groups density, and the presence of dangling hydrophobic groups are highly important factors to increase the mechanical properties and hydrophobicity of siloxane-based aerogels.…”
Section: Historical Strategy For Improvement Of Mechanical Propertiesmentioning
confidence: 99%
“…7,8 Schaefer et al have shown that the scattering profile of gels obtained from arylenebridged alkoxysilanes (EtO) 3 Si(C 6 H 4 ) n Si(OEt) 3 (n ) 1-3) was similar to that prepared from Si(OR) 4 . 9 Thus, the morphology is not qualitatively changed by the bridging organic groups which are integrated in the network. However, the case of 1 is different from that of (RO) 3 Si-X-Si(OR) 3 precursors because two different metal alkoxide moieties are involved.…”
Section: Introductionmentioning
confidence: 99%